If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(v + -1) = 4 Reorder the terms: 5(-1 + v) = 4 (-1 * 5 + v * 5) = 4 (-5 + 5v) = 4 Solving -5 + 5v = 4 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5v = 4 + 5 Combine like terms: -5 + 5 = 0 0 + 5v = 4 + 5 5v = 4 + 5 Combine like terms: 4 + 5 = 9 5v = 9 Divide each side by '5'. v = 1.8 Simplifying v = 1.8
| 2x-47+x=112 | | 7+c+12=-4c+12 | | 1=6(k+5) | | 7(x-4)=3(x-8) | | 4x+3=57-2x | | 2x-47=2(53)-47 | | 6r+11=15-r | | x^2+4x-94=0 | | 4-2(x+5)=4 | | 7(b-2)=4 | | 2(10-3d)+80= | | 3x+2-x=12 | | F(x+8)=3(x+8)-9 | | 7=8(r-6) | | 7(v+4)-3v=2(2v+2)-12 | | 0.04x^2-3.5x+100=10 | | 8x+17=5x+23 | | 18x+54=252 | | y=0.7x-3.6 | | 10+11x=-30+x | | -6(i-3)=2 | | 4x+6(x-4)=16 | | 22+4x=9x+2 | | -9(-6)-5(2)=12 | | 154x=462 | | -9(3)-5(-6)=12 | | 5x+5y+6z-2x+z-8y= | | 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x |